2022
DOI: 10.1029/2022gl098904
|View full text |Cite
|
Sign up to set email alerts
|

Record Low Antarctic Sea Ice Cover in February 2022

Abstract: Antarctic sea ice extent (SIE) has displayed a complex pattern of change over the period for which we have reliable data from passive microwave satellite instruments starting in the late 1970s. Until the mid-1990s there was no significant trend in the annual mean total Antarctic SIE or the extent at the annual minimum (Figure 1a). However, this was followed by an upward trend in both measures, which was accompanied by an increase in the inter-annual variability (Fogt et al., 2022, Figure 1). The overall increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
52
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(81 citation statements)
references
References 31 publications
2
52
0
Order By: Relevance
“…Antarctic sea ice plays an important role in the global climate system by reflecting the solar energy and modulating the surface water salinity (Goosse and Zunz, 2014;Massom et al, 2018;Maksym, 2019). In the context of global warming and the significant decline in Arctic sea ice cover, the Antarctic sea ice area has unexpectedly increased over recent decades (Zhang, 2007;Parkinson and Cavalieri, 2012;Comiso et al, 2017) but dropped to a historic low in 2017 and again in 2022 (Turner and Comiso, 2017;Turner et al, 2022). During 2016-2020, the sea ice coverage in the Southern Ocean did not recover and set eight new Antarctic monthly record lows instead (Parkinson and DiGirolamo, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Antarctic sea ice plays an important role in the global climate system by reflecting the solar energy and modulating the surface water salinity (Goosse and Zunz, 2014;Massom et al, 2018;Maksym, 2019). In the context of global warming and the significant decline in Arctic sea ice cover, the Antarctic sea ice area has unexpectedly increased over recent decades (Zhang, 2007;Parkinson and Cavalieri, 2012;Comiso et al, 2017) but dropped to a historic low in 2017 and again in 2022 (Turner and Comiso, 2017;Turner et al, 2022). During 2016-2020, the sea ice coverage in the Southern Ocean did not recover and set eight new Antarctic monthly record lows instead (Parkinson and DiGirolamo, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…1a). In February 2022, the SIE reached a new record low 44 . Observations and model experiments by prescribing observed tropical SST anomalies suggested that the 2016 extreme sea ice low was caused by (1) southward warm air advection associated with the zonal wave number 3 teleconnection pattern in the early austral spring induced by tropical SST anomalies, and (2) the strong negative SAM event in the late austral spring [38][39][40][41][42] .…”
mentioning
confidence: 99%
“…Sea ice, which shapes the entire marine ecosystem, has slightly increased in extent in the East Antarctic SO over the past decades, albeit with strong interannual variations. The unprecedented springtime retreats in 2016 and 2021/22 (Turner et al, , 2022 and generally lower summer extent since 2016 and 2021/2022 (compared to the 1981/2010 long-term mean) may indicate the onset of a circum-Antarctic decline of sea-ice extent (Rackow et al, 2022). Increased upwelling, probably associated with the Southern Annular Mode, is the most reasonable explanation for changes in nutrient concentrations in the upper water column in the Weddell Gyre since the 1990s (Hoppema et al, 2015).…”
Section: Geographical and Environmental Justificationmentioning
confidence: 98%
“…Over the recent decades, a slight increase in Antarctic sea-ice extent has been observed, with considerable spatial and temporal variabilities (Parkinson, 2019), even though the summer sea-ice minimum has been below the long-term trend in the past seven years, with a record low in February 2022 (Turner et al, 2022). However, the low sea-ice extent period is not yet long enough to conclude a regime shift or a change in long-term trends.…”
Section: Introductionmentioning
confidence: 99%